Estimation of Surface Runoff Volume in Wadi Al-Amghar Basin, Southwestern of Al-Muthanna Desert, Using the SCS-CN Method. (Iraqi National Journal of Earth Science (INJES), 2026)
Wadi Al-Amghar Basin, located in the southwestern part of Al-Muthanna desert, is characterized by extreme aridity due to the scarcity of rainfall over the basin and its surrounding lands. The availability of water in the basin depends on the amount of rainfall during the winter season, as well as the inflow of water into the basin from the northern parts due to the slope gradient. However, part of this water fails to generate surface runoff due to the nature of the prevailing soil, which reduces the formation of surface runoff. Nevertheless, this does not negate the existence of runoff, as the layer beneath the sandy surface is an impermeable layer with low permeability, which allows for the formation of surface runoff. Additionally, the soil in the basin is not entirely loose; it contains a high proportion of rocks and stones. For this reason, the study relied on the amount of rainfall, which was measured at 113.9 mm during the study period extending from 2000 to 2023. The Soil Conservation Sevice Curve Number (SCS-CN) model is employed to estimate the volume of surface runoff due to its reliability utilizing Geographic Information Systems (GIS) for more accurate data. The results reveal that the basin is capable of generating surface runoff with high CN values covering an area of 1,018.03 km² representing 57.23% of the basin’s total area. This indicates that more than half of the basin's area has the potential to generate surface runoff.
Keywords: Surface runoff, SCS-CN, Al-Amghar, Water